Integrating paleoparasitological, paleogenetic, and archaeological data to understand the paleoecological scenario of pre-Columbian archaeological site Gruta do Gentio II, Brazil - Gurjão, Ludmila; Brito, Lorrayne; Dias, Ondemar; Neto, Jandira; Iñiguez, Alena Mayo (Frontiers in Microbiology, 2025)
Paleoparasitology and paleogenetics is the study parasites in ancient remains from latrines, mummified individuals, and coprolites, that is fossilized or desiccated feces. Paleoparasitological studies in Brazil began with analyses of coprolites from the Gruta do Gentio II (GGII) archaeological site, the oldest site related to the Una ceramist tradition (12,000 to 410 BP), Brazil. The GGII archaeological site contained numerous human burials, lithics, and cultural artifacts such as basketry, ceremonial ornaments, and unique pottery of the Una tradition. Coprolites of GGII were submitted to paleoparasitological, and paleogenetic analyses for parasite identification and coprolite origin. In addition, the archaeological characterization of the GGII site was integrated into paleo analyses for proposing a paleoecological scenario. Five taxa of parasites, including Ancylostomidae, Echinostoma sp., Spirometra sp., and Trichostrongylus sp., and three different morphotypes of Capillariidae were recognized in multiple coprolites that were distributed heterogeneously in several stratigraphical layers. The origin of coprolites was genetically defined as five species of mammals, humans, felines as Panthera onca and Leopardus pardalis, and marsupials as Didelphis albiventris and Philander opossum. This is the first study in Brazil that identified both, parasites and species of animals in Pleistocene/Holocene producers of coprolites with geographical and temporal information. The integration of paleoparasitology, paleogenetics, and archaeology is essential to propose paleoecological scenarios from the past of Brazil.